STUDI KOMPARATIF HASIL BELAJAR MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH MTs N 2 - Chumairoh, Chumairoh; Buwono, Sri; G. S, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to know the difference result of social studies learning by using cooperative learning type make a match in class VIII D and VIII E of MTs N 2 Pontianak. The main problem of this research is, â€œis there any differences on studentâ€™s result in social studies learning by using cooperative learning make a matchÂ method in class VIII D and VIII E of MTs N 2 Pontianakâ€. The specipic problem of thie research is â€œhow is the imlementation of using cooperative learning make a match method in class VIII D and VIII E of social studies learning MTs N 2 Pontianak? How is the result of social studies learning by using make a match method in class VIII D and VIII E of MTs N 2 Pontianak? Is tere any differences on students result in social studies learning by using make a match method in class VIII D and VIII E of MTs N 2 Pontianak?â€. The variable in the research is cooperative learning make a match method and social studies result. Pre-experimental one shoot case study is the method that used in this research. Participants of the research are class VIII D dan VIII E in total 74 students. Data is collected by using direct communication technique, direct observation technique, documentary study technique and measurement technique. The results showed that using by make a match method, the mean score of class VIII D is 10,24 and class VIII E is 10, 62. Next, t-test is used to explaine either there is any differences. T-test showed tcount < ttable, because tcount < ttable -1,633 < 1,993 so Ho is accepted and there is no difference in students result in social studies learning by using cooperative learning make a match method between class VIII D and VIII E of MTs N 2 Pontianak.Â Keywords : Â Cooperative learning make a match method, learning result, social studies lerningÂ